Allied Failure in the Norwegian Littoral, 1940-Operational Level of War for Today - Brown, Carradean L. (1994)
Allied operations and strategy in the spring 1940 Norwegian campaign which ended with the evacuation of Narvik are analyzed. These operations were the first joint, combined warfare in WWII and conducted in a littoral environment. They provide valuable operational level of war lessons to current day commanders and planners of the United States Armed Forces who will direct decreased forces in various littoral environments around the world. The majority of this analysis relies on sources written from the British perspective. Limited views of the strategy and operations from the Norwegian and German side are presented. Main causes of the Allied failure include: unclear strategic and operational objectives failure to provide unity of command, national command authority interference in theatre operations, intelligence shortfalls, lack of sustainable logistics and insufficient force. A conclusion is reached that these issues still present potential problems and require continued consideration in modern U.S. military planning. Allied failure in the norwegian littoral, 1940- Operational level of war lessons for today